The role of 11 beta-hydroxysteroid dehydrogenase in maturation of the intestine - Pohlová, I; Miksík, I; Pácha, J (Mechanisms of ageing and development, 1997)
Glucocorticoids promote the development of many organs including intestine. At the cellular level, the activity of glucocorticoids is regulated by 11 beta-hydroxysteroid dehydrogenase (11 beta HSD) which converts active glucocorticoids to inactive metabolites. As 11 beta HSD is also expressed in the intestine, this enzyme may be an important regulator of intestinal maturation. To investigate this, we have performed the systematic study of the development of intestinal 11 beta HSD activity and its cofactor preference as well as of the effect of 11 beta HSD inhibition by carbenoxolone on postnatal development of sucrase, alkaline phosphatase and Na,K-ATPase in the intestine. The activity of 11 beta HSD was low in ileum of suckling rats and significantly increased during the weaning period. In colon, the activity was already high in suckling rats and gradually rose during the postnatal development. 11 beta HSD activity was undetectable in jejunum both in young and adult rats. At 14.5 nM corticosterone, colonic 11 beta HSD utilized predominantly NAD as a cofactor, but displayed significant sensitivity also to NADP. Ileal 11 beta HSD had similar sensitivity to both cofactors. With NAD as a cofactor, ileal 11 beta HSD had a Km (59 +/- 10 nM) compatible with the colonic enzyme (81 +/- 14 nM). Carbenoxolone administration to suckling and weanling rats in vivo did not result in any changes of sucrase activity in jejunum and ileum, alkaline phosphatase activity in ileum and distal colon or Na,K-ATPase activity in ileum. However, carbenoxolone significantly increased Na,K-ATPase activity in distal colon. Our results indicate that the high-affinity type of 11 beta HSD is expressed not only in colon but also in ileum and that 11 beta HSD is an important factor in the regulation of tissue levels of active glucocorticoids in developing colon but not in the small intestine.
Keywords: Sucrase; Alkaline Phosphatase; alkalická fosfatasa; střeva; Intestines; 11-beta-hydroxysteroiddehydrogenasy; střevní sliznice; odstavení; krysa rodu Rattus; sacharasa; zvířata; Carbenoxolone; potkani Wistar; sodíko-draslíková ATPasa; Rats, Wistar; karbenoxolon; Hydroxysteroid Dehydrogenases; inhibitory enzymů; Rats; Sodium-Potassium-Exchanging ATPase; hydroxysteroiddehydrogenasy; Animals; Enzyme Inhibitors; Intestinal Mucosa; Weaning; 11-beta-Hydroxysteroid Dehydrogenases